Pengembangan Puzzle Kreatif Untuk Media Pembelajaran Anak Sekolah Dasar - Alzanah, Lulu; Dewi, Happy Indira (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
The background of the research is that there has not been developed learning media that attractsstudents' interest and motivation to learn which has an impact on student learning outcomes which are stilllow. The type of research is research and development (R&D). The development model used is the ADDIE ,which includes analysis, design, development, implementation, evaluation. This research develops learningmedia in the form of creative puzzles for elementary school children. The development of creative puzzlelearning media for Pancasila material is carried out through the potential and problem stage, the datacollection stage, the product design stage, the product validation and testing stage (small scale), the revisionstage, and the product use stage in the classroom. Based on media and material experts, the creative puzzlelearning media for Pancasila material is very suitable to be used as a learning medium by making revisionsaccording to expert suggestions and comments. The percentage of eligibility given by media experts is96.67% and material experts is 94.55%. Creative puzzle learning media for Pancasila material receivedpositive responses from students and teachers, and was effective for use in improving thematic learningoutcomes of the theme of my experience as indicated by an increase in the value of learning outcomes. Theaverage learning outcomes before using creative puzzle learning media was 64.08 and after using creativepuzzle learning media an average of 78.28 with an increase of 22.16%.